Bioenergetic Analysis of FLAG Tagged-Subunit 8 of Saccharomyces cerevisiae Mitochondrial ATP Synthase - I MADE ARTIKA (Microbiology Indonesia, 2010)
The majority of cellular energy in the form of adenosine triphosphate (ATP) is synthesized by the F1F0-ATP synthase. The yeast mitochondrial F1F0-ATP synthase is a multisubunit complex that contains at least 17 different subunits grouped into F1 and F0 sectors. Subunit 8 of yeast mitochondrial ATP synthase is a hydrophobic protein of 48 amino acids encoded by the mitochondrial ATP8 gene. Subunit 8 has three distinct domains; an N-terminal domain, a central hydrophobic domain and a C-terminal domain. FLAG tag addition to the C-terminus of subunit 8 and its variants has facilitated elucidation of subunit 8's membrane topology. In order to analyze its detailed structure and function, a set of strains expressing FLAG tagged-subunit 8 and its variants were subjected to bioenergetic analysis at cellular and mitochondrial levels. Results obtained showed that the hydrophobic character of the central hydrophobic domain of subunit 8 is essential for functional coupling between F1 and F0 sectors, hence for mitochondrial ATP synthase function.